Clinical implementation of noninvasive prenatal testing among maternal fetal medicine specialists†. (12th February 2014) - Haymon, Lori; Simi, Eve; Moyer, Kelly; Aufox, Sharon; Ouyang, David W.
ABSTRACT Objective To assess the clinical implementation of non‐invasive prenatal testing (NIPT) among maternal‐fetal medicine (MFM) specialists. Method Practicing MFMs were invited by email to complete questionnaires via SurveyMonkey©. Results Of 278 respondents, 56% were male, 48% practiced in academic centers, and 94% currently offer NIPT. NIPT is most often being offered 'to specific patients meeting certain criteria' (59.2%), for indications of advanced maternal age (87.5%), abnormal screen results (94.9%), abnormal ultrasound findings (90.2%), and 'when a high‐risk patient declines invasive diagnostic testing' (73.7%). Thirteen percent indicated NIPT is being offered as a diagnostic test. Regardless of whether NIPT was presented as a diagnostic or screening test, 65.3% of MFMs estimate 'some' of their patients have undergone invasive testing for confirmation. Responses were mixed concerning appropriate populations and diagnostic capabilities of NIPT, but MFMs generally agree NIPT should be confirmed with invasive testing and will replace conventional screening procedures. Conclusion Assessment indicates NIPT is being adopted by MFMs, largely in accord with recently published American College of Obstetricians and Gynecologists and the Society for MFM guidelines. Cost and test performance remain factors for not adopting NIPT. Further research on clinical management based on NIPT results and patient understanding of NIPT results is suggested. © 2013 John Wiley & Sons, Ltd.